Cervical laminoplastic in patients with cerebro-spinal cord injury - Salkov, Mykola; Оvcharenko, Dmitry (ScienceRise: Medical Science, 2018)
Cervical laminoplasty is a surgical method of treating the stenosis of the spinal canal in the cervical region, which increases the intraspinal space and allows preserving the integrity of the posterior elements of the vertebrae. Purpose: The aim of the study was to investigate the efficacy and develop the treatment tactics for patients with posttraumatic cervical spondylotic myelopathy due to stenosis of the spinal canal. Materials and methods. On treatment in "Dnepropetrovsk Regional Clinical Hospital after named I.I. Mechnikov ", from April 2014 to February 2018 there were 7 patients with posttraumatic cervical spondylotic myelopathy due to stenosis of the spinal canal. The age of the patients was 54-68 years. To assess the effectiveness of the treatment, the ASIA neurological disorders scale was used. The degree of severity of neurological disorders of patients corresponded to C-D. All patients underwent standard SCT and MRI study. Results of the study. In the early postoperative period, 6 patients showed improvement in their neurological status. Patients of group C - 2 observations (before surgery, muscle strength in the limbs was below 3 points), recovered to category D (muscular strength was more than 3 points). In patients included in the category D - 4 examinations (before surgery, muscle strength was more than 3 points, but did not reach 5 points), there was a complete restoration of muscular strength in the limbs - 5 points. One patient in Group D did not have a neurological recovery. Conclusions: 1. The operation is organ-preserving and after the operation the spinal cord remains covered with a bone tissue behind it, which prevents the formation of scar tissue directly on the dura mater. 2. Decompression of the spinal cord is achieved without significant disruption of stability, thus reducing the likelihood of postoperative kyphotic deformity and spondylolisthesis. 3. Laminoplasty does not require subsequent spondylodesis, movement remains in the segment, in contrast to the methods that include the installation of the fixation structure, in this connection, the severity of degeneration at adjacent levels may decrease. 4. Carrying out decompressive laminoplasty in patients with traumatic myelopathy, most effective in the early days after trauma, the first 7 days